The A.P Møller shares, the US dollar and the price of oil - Ole Risager (Copenhagen Business School (CBS), Department of Economics, 2003)
1. Brief Introduction. The two companies D/S Svendborg and D/S 1912 have for almost a century been the parent companies of the A.P. Møller Group. These companies were founded by Mr. Arnold Peter Møller and his father Captain Peter Mærsk Møller. They were in the beginning entirely into shipping. In 1912, the fleet consisted of 6 vessels. Much has happened since the company was founded: The A.P. Møller Group has by any standards become the biggest company in Denmark. Moreover, “Svendborg" and “1912" have recently been merged into one company “A.P. Møller – Mærsk A/S". However, as we shall be concerned with the performance of the company also in the past we will repeatedly make reference to the historic parent companies. As “Svendborg" and "1912" grew bigger they expanded into a number of other businesses.
hdl:10398/7627
Keywords: H00; 330; Shipping and Offshore Activities; Oil and Gas